AYAT TENTANG WAKTU DALAM KARYA LUKIS KALIGRAFI KONTEMPORER - Afizah Afizah; Syafei Syafei (Universitas Negeri Padang, 2021)
The purpose of making this final work is to visualize the verses of the Al-Qur’an about the regrets of time through contemporary calligraphy paintings, it is hoped that i can add insight and knowledge for the community on this matter. The method in making this work goes through several stages, namely : (1) preparation, (2) elaboration, (3) synthesis, (4) concept realization and (5) completion, display, documentation and reporting. The works that are presented for exhibition are as follows : The first “Diperlihatkan”, second “Tak Berguna”, third “Penghuni Neraka”, fourth “Demi Masa”, fifth “Peringatan”, sixth “Penyesalan Kehidupan”, seventh “Ingin Kembali Kedunia”, eighth “Permohonan”, the ninth “Lalai dan Tak Beriman”, tenth “Lalai dalam sholat”.Kata Kunci : Kaligrafi Arab, Waktu, Penyesalan